PENGARUH PROFITABILITAS DAN PERTUMBUHAN PENJUALAN PADA NILAI PERUSAHAAN - Candani, Novi; Badera, I Dewa Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
Companies that have gone public generally seek to increase investor prosperity by increasing the value of the company. Company value is a condition that can be achieved by a company as an illustration of public trust in the company after going through a process of activity since the company was founded to its current state. The study was conducted to identify and empirically test the effect of profitability and sales growth on firm value. The research was conducted on basic and chemical industrial sector companies for the 2017-2019 period with a research sample of 51 companies so that 151 observations were obtained. The results of the data analysis carried out obtained 1) profitability has a positive effect on firm value, meaning that the higher the firm's profitability, the higher the firm value. 2) sales growth has a positive effect on the value of the company, this shows that sales growth that increases will cause the value of the company to also increase, and vice versa. Based on the results obtained, the research can be used as a reference and material for further research development and supports signaling theory which explains that good quality companies deliberately give signals to the market.